Day 1 Tue, October 27, 2015 2015
DOI: 10.4043/26067-ms
|View full text |Cite
|
Sign up to set email alerts
|

Unique Hybrid Drill Bit with Novel PDC Cutters Improves Performance in Ultra-Deepwater Brazil Pre-Salt Application

Abstract: The Brazil ultra-deepwater, pre-salt application has been a very challenging drilling environment since exploration activity began in 2005. The initial pre-salt section contains limestone with random silicified nodules. Over the last few years, operators have collected large amounts of data for service companies to analyze to improve drilling performance through bit design. Using this information, a hybrid bit design with the most advanced cutter and bit technology was developed successfully increasing the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Up to now, various new special-shaped PDC cutters such as conical, ridged PDC cutter have been developed [9]. Field drilling tests show that, special-shaped PDC cutters show certain advantages in hard rock drilling, for example, the conical PDC cutter developed by Smith Company can better concentrate the load on one point to break the rock, and its thicker diamond layer helps to improve the wear resistance and stability of the cutter [10,11]; the diamond layer of the ridged PDC cutter has a ridge-like structure, which shows higher hardness and toughness [12,13]; the multi-dimensional special-shaped PDC cutter developed by Baker Hughes Company (https://www.bakerhughes.com/) helps to improve the heat conversion efficiency, and maintain its aggressiveness for a long time [14,15].…”
Section: Figure 1 Pdc Drill Bit Wear Photomentioning
confidence: 99%
“…Up to now, various new special-shaped PDC cutters such as conical, ridged PDC cutter have been developed [9]. Field drilling tests show that, special-shaped PDC cutters show certain advantages in hard rock drilling, for example, the conical PDC cutter developed by Smith Company can better concentrate the load on one point to break the rock, and its thicker diamond layer helps to improve the wear resistance and stability of the cutter [10,11]; the diamond layer of the ridged PDC cutter has a ridge-like structure, which shows higher hardness and toughness [12,13]; the multi-dimensional special-shaped PDC cutter developed by Baker Hughes Company (https://www.bakerhughes.com/) helps to improve the heat conversion efficiency, and maintain its aggressiveness for a long time [14,15].…”
Section: Figure 1 Pdc Drill Bit Wear Photomentioning
confidence: 99%
“…The test results showed that this type of hybrid bits was capable to drill in hard or heterogeneous formation with high efficiency, more particularly, both the torque and the torsional vibration of the bit were lowered, and the stick-slip effect was reduced. [17][18][19][20] As a new bit type, study on the rock-breaking method of this hybrid drill bit can seldom be found. For further study on it, the Rock Bit Laboratory of SWPU (Southwest Petroleum University) has conducted a series of systematic research on the hybrid bit technology 21,22 and has achieved some research findings.…”
Section: Introductionmentioning
confidence: 99%